Non-linear waves in heterogeneous elastic rods via homogenization - De Luna, M; Duričković, B; Goriely, A (2012)
We consider the propagation of a planar loop on a heterogeneous elastic rod with a periodic microstructure consisting of two alternating homogeneous regions with different material properties. The analysis is carried out using a second-order homogenization theory based on a multiple scale asymptotic expansion. © 2011 Elsevier Ltd. All rights reserved.